Beneficial effects of leptin substitution on impaired eating behavior in lipodystrophy are sustained beyond 150 weeks of treatment. (January 2019) - Püschel, Janett; Miehle, Konstanze; Müller, Karsten; Villringer, Arno; Stumvoll, Michael; Fasshauer, Mathias; Schlögl, Haiko
Abstract: Aim: Metreleptin treatment in lipodystrophy patients improves eating behavior with increased satiety and reduced hunger. However, no data are available whether effects are maintained beyond 52 weeks of treatment. Methods: A prospective study with measurements at baseline and at >150 weeks of metreleptin treatment was performed. Five female lipodystrophy patients with indication for metreleptin were included. Behavioral aspects of hunger- and satiety regulation were assessed by validated eating behavior questionnaires and visual analog scales assessing hunger and satiety feelings before and after a standardized meal. Results: Hunger rated on visual analog scales at 120 min after the meal significantly decreased from 46 ± 10 mm at baseline to 17 ± 6 mm at long-term assessment. Furthermore, satiety at 5 and 120 min after the meal significantly increased from baseline to long-term assessment (5 min: 70 ± 7 mm to 87 ± 3 mm; 120 min: 43 ± 10 mm to 79 ± 8 mm). On the Three Factor Eating Questionnaire, the mean value of factor 3 (hunger) significantly decreased from 9.2 ± 0.2 at baseline to 2.6 ± 1.5 at long-term assessment. In the Inventory of Eating Behavior and Weight Problems Questionnaire, mean values for scale 2 (strength and triggering of desire to eat) and scale 7 (cognitive restraint of eating) significantly decreased from baseline (31.6 ± 4.8 and 11.4 ± 2.2, respectively) to long-term assessment (14.0 ± 2.1 and 10.0 ± 1.9). Conclusion: First evidence is presented that long-term metreleptin treatment of >150 weeks has sustained effects on eating behavior with increased satiety, as well as reduced hunger and hunger-related measures.